Research on the mechanism of pore structure on water transportation in cement-based materials - Enze Hao; Yuhang Li; Dali Zhang; Wenbang Zhu; Ruiming Liu; Xinjie Wang; Yali Cao; Yali Gu; Xiumei Zheng (PLoS ONE, 2025)
To explore the mechanism of water transport in cement-based materials with different water-cement ratios under the influence of pore structure, three types of specimens with different water-cement ratios, namely paste, mortar and concrete, were fabricated. The capillary water absorption and isothermal adsorption-desorption water transport characteristic values of the three types of cement-based materials were studied, and the pore changes and porosity were analyzed. The test results show that for the cement-based materials with the same water-cement ratio, the water absorption and water absorption rate of the paste are greater than those of the mortar and concrete, and the porosity of the paste is greater than that of the concrete and mortar. Based on Darcy’s law, a water transport model based on different porosity parameters was established. The results show that the water transport speed of the paste is greater than that of the mortar and concrete, which is in good agreement with the experimental results.